PENGARUH PENGALAMAN MAGANG DAN BIMBINGAN KARIR TERHADAP KESIAPAN KERJA SISWA KELAS XII DI SMKS NU GRESIK TAHUN AJARAN 2024 / 2025 - Raharjo, Mutiara Wijaya; Marlena, Novi (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
Work readiness can be defined as the ability of students to enter the workforce immediately after graduating from school, equipped with the mental preparedness, knowledge, experience, and maturity they have acquired. Therefore, readiness is essential for employment. Work readiness is a crucial aspect that must be possessed by students of Vocational High Schools (SMK) in order to compete in the job market after graduation. Factors that may influence work readiness include internship experience and career guidance obtained by students during their education. This study aims to analyze the influence of internship experience and career guidance on the work readiness of XII grade students at SMKS NU Gresik in the 2024/2025 academic year. This research uses a quantitative method. The research was conducted at SMKS NU Gresik with XII grade students as the research population. The sampling technique used a census method, resulting in 129 students from all majors being selected as research samples, with the criteria that they had participated in internship programs and received career guidance at school. The instrument used in this study was a questionnaire, and the data were analyzed using multiple linear regression with SPSS version 26. The results showed that internship experience and career guidance had an influence on the work readiness of XII grade students at SMKS NU Gresik in the 2024/2025 academic year. Keywords : work readiness; internship experience; career guidance; students